2019
DOI: 10.7554/elife.49539
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of the Ska-Ndc80 interaction and their influence on microtubule tracking and force-coupling

Abstract: Errorless chromosome segregation requires load-bearing attachments of the plus ends of spindle microtubules to chromosome structures named kinetochores. How these end-on kinetochore attachments are established following initial lateral contacts with the microtubule lattice is poorly understood. Two microtubule-binding complexes, the Ndc80 and Ska complexes, are important for efficient end-on coupling and may function as a unit in this process, but precise conditions for their interaction are unknown. Here, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 100 publications
(248 reference statements)
12
69
1
Order By: Relevance
“…Nevertheless, our data are consistent with in vitro biophysical experiments that demonstrate how CENP-F can function as a force transducer (Kanfer et al, 2017;Volkov et al, 2015). This is, however, distinct from the Ska complex, which has a well-established forcetransducing role in vitro and during congression in vivo (Auckland et al, 2017;Helgeson et al, 2018;Huis In 't Veld et al, 2019b). We did not find a substantial role for CENP-F in congression and also found no additive defects when the Ska complex was depleted in CENP-F mutant cells (not depicted), thus ruling out any redundancy.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, our data are consistent with in vitro biophysical experiments that demonstrate how CENP-F can function as a force transducer (Kanfer et al, 2017;Volkov et al, 2015). This is, however, distinct from the Ska complex, which has a well-established forcetransducing role in vitro and during congression in vivo (Auckland et al, 2017;Helgeson et al, 2018;Huis In 't Veld et al, 2019b). We did not find a substantial role for CENP-F in congression and also found no additive defects when the Ska complex was depleted in CENP-F mutant cells (not depicted), thus ruling out any redundancy.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Helgeson et al (2018) used optical trapping assays to show that Ska complexes can impart almost wildtype end-tracking activity to tail-less NDC80 complex-coated beads on depolymerizing microtubules, even under applied force. Similarly, Huis in't Veld et al (2019) demonstrated that Ska complexes can restore end-tracking activity to oligomerized tailless complexes in the absence or presence of applied force. These results raise the possibility that the Ska complex may be able to, at least in part, compensate for the Hec1 tail domain in human cells.…”
Section: Compensation For Hec1 Tail Function By Co-factorsmentioning
confidence: 90%
“…Furthermore, a recent study by Huis in't Veld et al (2019) investigated how the phosphorylation state of the Hec1 tail domain impacted the ability of human NDC80 complexes to maintain attachments to depolymerizing microtubules in vitro. The authors reported that while the phosphorylation state of the tail did not affect the ability of trimerized, bead-bound NDC80 complexes to track with depolymerizing microtubules in the absence of tension, when a resisting force was applied with an optical trap, phosphorylated NDC80 complexes detached from depolymerizing microtubules with significantly higher frequency than non-phosphorylated complexes (Huis in't Veld et al, 2019). These results suggest that, at least in vitro, Hec1 tail phosphorylation affects the ability of human NDC80 complexes under tension to transduce forces from depolymerizing microtubules.…”
Section: The Hec1 Tail Domain and Microtubule Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations